Social determinants as a way to promote health in prenatal care: perception of primary care professionals - Carolina Gabriele Gomes da Rocha; Ivonete Teresinha Schulter Buss Heidemann; Jeane Barros de Souza; Michelle Kuntz Durand; Kamila Soares Maciel; Marli Terezinha Stein Backes (Universidade Federal de Santa Maria, 2021)
Objective: to understand the perception of primary care professionals about the influence of social determinants in promoting the health of pregnant women in prenatal care. Method: qualitative study, participant action type, based on Paulo Freire's Research Itinerary, developed through Thematic Investigation, Codification and Decoding and Critical Unveiling, which consists of data analysis. Two Culture Circles were held in a Health Unit, between July and October 2019, with 18 health professionals. Results: two themes were investigated: one reflects the determinants involved in prenatal care, and the other discusses prenatal care and determinants as a way to promote health. They revealed the relevance of knowing the determinants involved in the daily lives of pregnant women and which should be considered in full. Conclusion: there are multiple barriers faced by pregnant women in prenatal care, and it is necessary to strengthen these women with health-promoting care and linked to social determinants.